Isolation and Production of Proteolytic Enzyme by Bacterial Strains by Using Agrowates as Substrate - Masi, Chandran; Balaji, E.; Vigneshwar, J.; Chandramohan, C.; Fazil Ahmed, M.; Parthasarathy, N. (Asian Journal of Chemistry, 2014)
Protease production was investigated using Enterococcus hirae, Acinetobacter pittii and Pseudomonas aeruginosa isolated from dairy effluent. Different agro wastes such as mustard oil cake, roasted bengal gram peel, yellow split bean peel, coconut oil cake, sesame oil cake, groundnut oil cake, black gram peels are evaluated to check the possibility of potential utilization as substrates for protease production. Enterococcus hirae is found to produce maximum amount of protease (300 μg/mL) in casein than Acinetobacter pittii and Pseudomonas aeruginosa. The results showed that under optimized conditions among the various oil cakes and peels, protease production is at its peak in black gram peel at 48 h in Acinetobacter pittii (310 μg/mL) Pseudomonas aeruginosa (510 μg/mL) and Enterococcus hirae (610 μg/mL) but predominant production by Enterococcus hirae. Among the tested protein substrates, black gram peel served as the most preferable substrate for protease production and Enterococcus hirae as potential bacterial strain for protease production.